(untitled) - Wicander, Reed (Australia, 2006)
The book presents the content and material on plate tectonics in the first two chapters and offering more material on earth history than other texts in the market. The authors provide engaging examples, as can be seen in the "Cultural Connection" boxes. Chapter opener objectives are now numbered so that students can easily recognize the crucial points of the chapter while reading and then they are numbered again in the chapter summary, for review. The Fourth Edition has numerous new photos that will be of interest to faculty and students
Keywords: Geology